(untitled) (Journal of Universal Science Research, 2023)
The 19th century in England is commonly referred to as the Victorian. From the factual side, this is not entirely true: Queen Victoria ascended the English throne only in 1837 (and remained on it for more than sixty years). The century began with long wars with Napoleon, then came the years of political reaction. In literature, the beginning of the century was the era of the Romantics. In 1798, two young poets, William Wordsworth and Samuel Coleridge, published a book of poems, Lyrical Ballads. Wordsworth wrote a preface to it, perceived as a manifesto for a new literary school. In England, the era of romanticism turned out to be shorter than in other countries - only three decades. But for the richness of talents, for the brightness of artistic accomplishments, it can hardly be compared with any other period in the history of English literature.